La théorie néo-classique de la demande de capital : problèmes théoriques de spécification - Loranger, Jean-Guy (L'Actualité économique, 1976)
AbstractThis paper is a critique of the neoclassical theory of investment behavior advanced by Jorgenson and others. The main conclusions are as following:Jorgenson's specification of the objective function implies that prices are constant.The rejection of this hypothesis and the assumption of a competitive equilibrium imply that prices must be treated as exogeneous variables and that there is no excess capacity of production.Jorgenson's specification of an "ad hoc" adjustment between actual and desired demand for capital is not acceptable with respect to his equilibrium conditions.Since the capital stock is by definition a weighted sum of past investment, it would be more convenient to assume a hyperbolic function about replacement instead of a geometric function.The rejection of the competitive equilibrium assumption in favor of a non competitive equilibrium approach implies that prices must be considered as endogeneous variables and that an excess capacity of production is always possible. This last consideration is crucial when interpreting the empirical results obtained by estimating the parameters of a "reduced form" demand function for capital.